GENERAL CHARACTERISTICS OF INTERMEDIATE MASS FRAGMENT INCLUSIVE CROSS SECTIONS IN 20Ne INDUCED INTERACTIONS - Papadakis, N. H.; et al., - (HNPS Advances in Nuclear Physics, 2020)
Inclusive integrated cross sections of intermediate mass fragments have been measured in 20Ne induced reactions on silver and gold targets at 20, 30, 40, 50 and 60 MeV/nucleon incident energies. Whereas the production yields remain approximately constant for the Ne+Ag system, for incident energies greater than 30 MeV/nucleon, they increase by a factor of 3.5 for the Ne+Au system over the full energy range studied.